The Rise of Functional Tic-Like Behaviors: What Do the COVID-19 Pandemic and Social Media Have to Do With It? A Narrative Review - Martindale, Jaclyn M.; Mink, Jonathan W. (Frontiers in Pediatrics, 2022)
Background: There has been a rise in explosive onset of tic-like behaviors during the COVID-19 pandemic. Historically, this is an uncommon phenomenology of functional movement disorders across all ages. Both the psychological burden of the pandemic and social media usage have been implicated in the rise of these tic-like behaviors. Methods: This paper provides a narrative review of the literature on chronic tic disorders, functional tics, and mass functional illness with particular focus on the key distinguishing features, role of social media, and the role of COVID-19. Results: The COVID-19 pandemic has profoundly affected the mental health of many individuals, including children, adolescents, and their caregivers. Implementation of lockdowns, lifestyle disruptions, school closures, and social distancing have driven a surge in social media and digital technology use. The combination of predisposing factors, the psychological burden of the COVID-19 pandemic, and social media are implicated in the rise and spread of tic-like behaviors; which may represent a modern-day form of mass functional illness. While many of the features overlap with functional tics, there are emerging distinctive features that are important to recognize. A more encompassing term, Functional Tic-Like Behaviors, is used to better reflect multiple contributing factors. Conclusion: Knowledge of these differences is essential to mitigate downstream health effects and poor outcomes.